2018
DOI: 10.3389/fpls.2018.01677
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Effects and Epigenetic Memory in the Clonal Plant Trifolium repens

Abstract: Transgenerational effects (TGE) can modify phenotypes of offspring generations playing thus a potentially important role in ecology and evolution of many plant species. These effects have been studied mostly across generations of sexually reproducing species. A substantial proportion of plant species are however reproducing asexually, for instance via clonal growth. TGE are thought to be enabled by heritable epigenetic modification of DNA, although unambiguous evidence is still scarce. On the clonal herb white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 72 publications
6
52
1
Order By: Relevance
“…In the case of the herbaceous plant Campanulastrum americanum , individuals that experience excess light develop heritable high light tolerance, which serves to pre-adapt progeny and displays maternal transmission when crossed to corresponding shaded individuals [17,18]. Transgenerational effects of the environment on plant phenotype in natural populations can also affect drought response in species of Trifolium [19]. Not surprisingly, plants that reproduce asexually provide an excellent model for investigating epigenetic variation for environmental resilience in natural habitats.…”
Section: Epigenetic Control Of Phenotypic Plasticitymentioning
confidence: 99%
“…In the case of the herbaceous plant Campanulastrum americanum , individuals that experience excess light develop heritable high light tolerance, which serves to pre-adapt progeny and displays maternal transmission when crossed to corresponding shaded individuals [17,18]. Transgenerational effects of the environment on plant phenotype in natural populations can also affect drought response in species of Trifolium [19]. Not surprisingly, plants that reproduce asexually provide an excellent model for investigating epigenetic variation for environmental resilience in natural habitats.…”
Section: Epigenetic Control Of Phenotypic Plasticitymentioning
confidence: 99%
“…Although this may have changed if we had measured another set of phenotypic traits, it is important to note that T. brevicorniculatum has a wide ecological niche, accepting all types of moisture conditions (Luo & Cardina, 2012). Consequently, it is likely that water is a less crucial stressor and the transgenerational effects due to water were not evolutionary relevant for this species (Rendina González, Preite, Verhoeven, & Latzel, 2018). Also, it is important to emphasize that we found that the transgenerational effects on traits were expressed early on the ontogeny (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…How consistently maternal infection generates variation in offspring fitness and resistance depends on how the effects vary across genotypes and environments. Experiments that focused on maternal effects induced by insect herbivores have shown that maternal effects can be highly genotype specific (Agrawal, 2002;Holeski, Zinkgraf, Couture, Whitham, & Lindroth, 2013;Colicchio, 2017), and may vary across genotypes in different abiotic conditions (Vivas, Zas, Sampedro, & Solla, 2013;Münzbergová & Hadincová, 2017;Rendina González, Preite, Verhoeven, & Latzel, 2018;Vu, Chang, Moriuchi, & Friesen, 2015). Hence, how strong and durable the pathogen-induced priming effects are, may depend on the genotype-specific response to infection, and the quality and predictability of the environment that both mothers and their offspring encounter (Agrawal et al, 1999;Herman & Sultan, 2011;Luna et al, 2012;Kuijper & Hoyle, 2015;Mauch-Mani et al, 2017).…”
Section: Accepted Articlementioning
confidence: 99%